The use of ambroxol in various fields of medicine outside medical indications - A Review of the Current Literature - Maczkowska, Alicja; Tkaczyk, Aneta; Maczkowski, Bartosz; Sołtys, Mirosław; Mikler, Szymon; Dróżdż, Marek; Boral, Wiktoria; Puliński, Jan; Przelaskowska, Aleksandra; Marzec, Wiktoria (Quality in Sport, 2026)
Introduction: Ambroxol is a drug that has a multifaceted application in medicine. Its main effects are mucolytic, mucokinetic, anti-inflammatory, antioxidant and local anesthetic. Ambroxol is used in various fields of medicine, including in the treatment of respiratory diseases, supporting the production of surfactant, treating sore throat and neuropathic pain. Ambroxol has been identified as a component that enhances the enzymatic activity of mutated glucocerebrosidase resulting from various mutations resulting from misfolding mutations in the GBA gene [1]. Experimental studies are also underway on the treatment of neurodegenerative diseases such as Parkinson’s disease, amyotrophic lateral sclerosis as well as in the treatment of stroke and inhibition of Clostridioides difficile toxins TcdA and TcdB. This article highlights the variety of applications of ambroxol, which was initially used only in respiratory diseases. Study Objective: The aim of this article is to comprehensively review the literature on the use of ambroxol in various fields of medicine in order to expand the research and use of ambroxol in diseases beyond its registered indications. Materials and Methods: Electronic database including PubMed, science networks, Google Scholar, to identify studies and literature reviews on the use of ambroxol in various fields of medicine. State of the Art: This review examines the use of ambroxol beyond its medical indications, mainly emphasizing its use in neuropathic pain, Parkinson’s disease, amyotrophic lateral sclerosis, Gaucher’s disease. Attention is also paid to its use in stroke patients and in the inhibition of Clostridioides difficile toxins TcdA and TcdB. Conclusion: Ambroxol is an antitussive drug that has been used for years. More and more studies are available on the use of ambroxol beyond its medical indications, which show the validity of the concept of its use in other fields of medicine than respiratory diseases.